2012
DOI: 10.1007/s00264-012-1629-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor correlates with the advance of clinical osteosarcoma

Abstract: Purpose Osteosarcoma is the most common primary malignancy in orthopaedic surgery. Studies suggest that expression of VEGF and high vascularity within osteosarcoma may correlate with poor prognosis. The purpose of this study was to determine whether there was a correlation of VEGF expression with clinical tumour stage and metastasis. Methods This retrospective case series examined 54 cases of osteosarcoma patients who were treated during a ten-year period. Relevant clinical information included age, gender, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…Like HO, extraskeletal OS is a highly vascular lesion with high microvascular density(17). Angiogenic markers, such as tumor-derived VEGF expression, as well as indices of vascularity correlate with outcome in OS(18, 19). Elevated tumor and circulating VEGF levels are associated with pulmonary metastasis(20), although this is not a universal finding across all studies(17).…”
Section: Discussionmentioning
confidence: 99%
“…Like HO, extraskeletal OS is a highly vascular lesion with high microvascular density(17). Angiogenic markers, such as tumor-derived VEGF expression, as well as indices of vascularity correlate with outcome in OS(18, 19). Elevated tumor and circulating VEGF levels are associated with pulmonary metastasis(20), although this is not a universal finding across all studies(17).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of osteosarcoma have strongly suggested that higher VEGF expression and activity in primary tumor tissue correlates with increased local microvessel density, faster development of pulmonary metastasis, and poorer prognosis for osteosarcoma patients [40, 41]. An increasing number of studies are focusing on the associations among gene mutations (particularly SNPs), protein expression/activity, and tumor occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Напри-мер, локализованное дистальное поражение более 90% химиотерапевтически-индуцированного некроза опухо-ли в сочетании с радикальной резекцией обеспечивает 5-летнюю выживаемость более чем в 80% случаев. Так, например, есть работы, показывающие корреляцию между объемом некроза опухоли и прогнозом [19], уров-нем экспрессии VEGF с худшим прогнозом и возможно-стью применения таргетной терапии [20,21]. Некоторые авторы сообщают о лучшем прогнозе, если при морфо-метрическом исследовании обнаруживаются «большие и округлые» ядра неопластических клеток [22].…”
Section: архив патологии 5 2015unclassified